Optimal GenSet: Model Creation For Optimization - Eriksson, Rasmus; Lexander, Nellie (My University, 2022)
This project is carried out in collaboration between Volvo Penta and Chalmers University of Technology. This is a master’s thesis and the report outlines the overall work carried out by two Product Development students at Chalmers University of Technology. Volvo Penta is a company within the Volvo Group and manufactures products within the marine-and-industry segment. A generator set (GenSet) with a diesel engine, which the project focuses on, is necessary for a wide range of applications, for instance at hospitals or in mines. The reliability of the power source is of great importance whether it is for a constant supply or a back-up generator supplying energy to vital functions in the society. This project was initialized since one of the most challenging problems right now is the increase in global warming, which emissions from diesel engines contribute to. Volvo Group has its own targets that are within the line of the Paris Agreement, where Volvo Group has committed to the Science Based Targets initiative. Volvo Penta has set a target to absolute reduce greenhouse gases by 37.5% by 2034 and the overall goal for Volvo Group is to have net-zero greenhouse gas emissions by 2040. By constructing a model and methodology that enables Volvo Penta to find the most promising improvements for a GenSet engine, with the cost taken into account, this project can help Volvo Penta to lower the CO2 emissions. The report showed the workflow for concept selection by constructing a model and methodology. The course of action followed: technology research, screening technologies by using an elimination matrix, methodology research, model creation that combines technologies for improving the efficiency of the engine by using Matlab and Simulink, sensitivity analysis and multi-criteria decision-making matrix, to finally have three concepts. The final concepts were visualized. By using the created model, the three most promising combinations of technologies could be selected. The first one included turbo compound, continuously varying transmission, cylinder deactivation and thermal barrier coating. The second one contained turbo compound, continuously varying transmission, dynamic skip fire and thermal barrier coating. The third one consisted of turbo compound, continuously varying transmission, cylinder deactivation, thermal barrier coating and variable compression ratio. The increased efficiency respectively were 29.4%, 29.6% and 29.5%. The cost for the additional technologies was approximately between 66300-68300 SEK.
Keywords: GenSet, Diesel Engine, Volvo Penta, Optimization, Concept Selection